The Pharmacology, Efficacy, and Safety of Rivaroxaban in Renally Impaired Patient Populations. (13th March 2021) - Ashton, Veronica; Kerolus‐Georgi, Sylvia; Moore, Kenneth T.
Abstract: Rivaroxaban is a factor Xa inhibitor oral anticoagulant first approved for use in the United States in 2011. Under the drug class commonly termed direct oral anticoagulants, rivaroxaban is approved for the most indications within its class, 7 indications, which are: (1) reduction of risk of stroke and systemic embolism (SE) in nonvalvular atrial fibrillation, (2) treatment of deep vein thrombosis (DVT), (3) treatment of pulmonary embolism (PE), (4) reduction in the risk of recurrence of DVT and/or PE, (5) prophylaxis of DVT following hip or knee replacement surgery, (6) prophylaxis of venous thromboembolism in acutely ill medical patients at risk for thromboembolic complications not at high risk of bleeding, and (7) reduction of risk of major cardiovascular events in patients with chronic coronary artery disease or peripheral artery disease. Considering the relationship between cardiovascular disease, renal impairment, and the use of oral anticoagulants, the following targeted review was created. This review reports the results of the primary pharmacology, pharmacokinetic modeling, clinical safety and efficacy, and real‐world postmarketing effectiveness and safety of rivaroxaban in patients with various degrees of renal impairment. Based on these data, rivaroxaban is a viable option for when anticoagulation is needed in patients who have both cardiovascular disease and renal impairment. However, as with any therapy, the benefits and risks of intervention should be carefully assessed and balanced. Patients treated with rivaroxaban for several of its approved indications should have their kidney function assessed prior to and during continued therapy to ensure consistency with the drug label.